MODAL ANALYSIS OF POLE DESIGN OF THE STATIONS WITH REGARD TO ADDED MASSES OF SOIL - Tiutkin, O. L. (Science and Transport Progress, 2007)
In the article the results of modal analysis of metropolises station construction of pylon type of deep contour interval are represented. Comparison of results of calculation of station model without a surrounding array and taking into account added the masses of ground are conducted.